Using an overhead target increases volleyball-specific vertical jump performance - Yildiz, M.; Akyildiz, Z.; Clemente, F. M.; Yildiz, D. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2023)
In volleyball, spikes, and block jumps are among the most important movements when earning points and impacting performance. Many studies have found a greater jump height after acutely augmented feedback and extrinsic focus of attention on vertical jump height. However, there are limited studies on the long-term effects of using an overhead target on volleyball-specific vertical jumps (block and spike jumps). Therefore, the aim of the current study was to investigate the effects of using an overhead target on the vertical jump heights of volleyball players. Twenty-five professional male volleyball players (age: 24.44 ± 3.78 years; height: 1.82 ± 8.79 cm; body mass: 80.96 ± 9.37 kg) were randomly assigned either to the experimental group with an overhead target (OHT) (n = 9), group without an overhead target (WOHT) (n = 10), or the control group (n = 8). The OHT group performed vertical jumps with an overhead target before their regular training program, while the WOHT group completed vertical jumps without an overhead target before their regular training program. Meanwhile, the control group performed only their regular training program, which was a 5 week (3 days per week) program. All participants` spike jump (SPJ) and block jump (BJ) results were assessed before and after the intervention. A repeated-measures analysis of variance (3 × 2) did not reveal any significant between-group interactions for SPJ and BJ (F = 7.32, p < 0.11 and F = 1.59, p < 0.22 respectively), but significant results were found for the time effect (F = 96.33, p < 0.01 and F = 132.25, p < 0.01 respectively) and group × time interaction (F = 42.59, p < 0.01 and F = 61.52, p < 0.01, respectively). While the pre- and post-tests for BJ and SPJ values did not change in the control group (p > 0.05), both of these values increased in the OHT group (60.00 ± 5.95-67.44 ± 5.98 cm, p < 0.01 for d = 1.24 and 49.00 ± 6.74-56.22 ± 5.29 cm p < 0.01 for d = 1.19, respectively) and WOHT group (57.50 ± 4.86-60.50 ± 4.99 cm, p < 0.01 for d = 0.60 and 47.75 ± 4.65-50.25 ± 3.69 cm, p < 0.01 for d = 0.59). It has been suggested that trainers and professionals can use an overhead target to increase the BJ and SPJ heights of professional volleyball players.